"Let's put on our teaching face" : an investigation of teaching styles and their skillsets - Marrier D'unienville, Krystle (Department of Drama, 2016)
The following dissertation analyses teaching as a performance and argues that teachers "enrole" or "put on their teaching face" when in front of their learners (Whatman, 1997:182; Dobson, 2005:334). The dissertation investigates the benefit to teachers of learning the skills of an actor such as voice, breathing and relaxation techniques, movement and use of space, presence and mindfulness and improvisation. The research argues that actor training may lead to increased effective communication with an 'audience' of learners in order to transmit and transact information. The research process involved observation and analysis of 14 teachers in government schools in Cape Town, using 'performance' as an analytical framework for a total of 36 hours over the course of a month. Questions around the use of acting and drama training are explored, and ethnographic observation and auto-ethnography are used to further the analysis. Trends and patterns were noted in the field using observational research methods such as video-recordings, field notes and interviews with participants. The writer's position as researcher was adapted from outsider (interpretive ethnography) to insider (autoethnography) due to unforeseen circumstances. Findings included the recognition of the predominant teaching style in schools, namely the transmissive approach, the emphasis on content learning, the lack of self-reflexive practice and acute stress due to the pressures of the job. The difficulties teachers are confronted with in their day to day operations became apparent, resulting in possible disinterest in, and lack of time, for professional development. The researcher's position as reflective practitioner and the ethnographic observations of teachers in schools confirmed and reinforced that teachers would benefit from actor and drama training skills such as voice, movement, improvisations and role-play.